Strategic Human Resource Management as Ethical Stewardship - Caldwell, Cam (Journal of business ethics, 2011)
The research about strategic human resource management (SHRM) has suggested that human resource professionals (HRPs) have the opportunity to play a greater role in contributing to organizational success if they are effective in developing systems and policies aligned with the organization’s values, goals, and mission. We suggest that HRPs need to raise the standard of their performance and that the competitive demands of the modern economic environment create implicit ethical duties that HRPs owe to their organizations. We define ethical stewardship as a model of governance that honors obligations due to the many stakeholders and that maximizes long-term organizational wealth creation. We propose that if HRPs adopt an ethical stewardship framework and the qualities of transformative leaders, they will be more aware of their ethical duties to their organizations and more effective in helping their organizations to create increased wealth, achieve desired organizational outcomes, and establish work environments that are more satisfying to employees.